Hyperoxia During Exercise: Impact on Adenosine Plasma Levels and Hemodynamic Data - Boussuges, Alain; Rives, Sarah; Marlinge, Marion; Chaumet, Guillaume; Vallée, Nicolas; Guieu, Régis; Gavarry, Olivier (Frontiers in Physiology, 2020)
Adenosine is an ATP derivative that is strongly implicated in the cardiovascular adaptive response to exercise. In this study, we hypothesized that during exercise the hyperemia, commonly observed during exercise in air, was counteracted by the downregulation of the adenosinergic pathway during hyperoxic exposure. Methods: Ten healthy volunteers performed two randomized sessions including gas exposure (Medical air or Oxygen) at rest and during exercise performed at 40% of maximal intensity, according to the individual fitness of the volunteers. Investigations included the measurement of adenosine plasma level (APL) and the recording of hemodynamic data (ie cardiac output and systemic vascular resistances (SVR) using pulsed Doppler and echocardiography. Results: Hyperoxia significantly decreased APL (from 0.58+/-0.06 to 0.21+/-0.05µmol L-1, p<0.001) heart rate and cardiac output and increased SVR in healthy volunteers at rest. During exercise, an increase in APL was recorded in the two sessions when compared with measurements at rest (+0.4+/-0.4 vs +0.3+/-0.2µmol L-1 for medical air and oxygen exposures, respectively). APL was lower during the exercise performed under hyperoxia when compared with medical air exposure (0.5+/-0.06 vs 1.03+/-0.2µmol L-1, respectively p<0.001). This result could contribute to the hemodynamic differences between the two conditions, such as the increase in SVR and the decrease in both heart rate and cardiac output when exercises were performed during oxygen exposure as compared to medical air. Conclusion: Hyperoxia decreased adenosine plasma levels in healthy volunteers at rest but did not eliminate the increase in APL and the decrease in systemic vascular resistances during low intensity exercise.